Fatty acid changes in liver and plasma lipid fractions after safflower oil was fed to rats deficient in essential fatty acids - Johnson, R. R. (1967)
1. Fatty acid patterns of liver and plasma triglycerides, phospholipids and cholesteryl esters were determined at intervals during 24hr. after essential fatty acid-deficient rats were given one feeding of linoleate (as safflower oil). 2. Liver triglyceride, phospholipid and cholesteryl ester fatty acid compositions did not change up to 7hr. after feeding. Between 7 and 10hr., linoleic acid began to increase in all fractions, but arachidonic acid did not begin to rise in the phospholipid until 14–19hr. after feeding. 3. Oleic acid and eicosatrienoic acid in liver phospholipid began to decline at about the time that linoleic acid increased, i.e. about 9hr. before arachidonic acid began to increase. 4. Changes in linoleic acid, arachidonic acid and eicosatrienoic acid in phosphatidylcholine resembled those of the total phospholipid. Phosphatidylethanolamine had a higher percentage content of arachidonic acid before the linoleate was given than did phosphatidylcholine, and after the linoleate was given the fatty acid composition of this fraction was little changed. 5. The behaviour of the plasma lipid fatty acids was similar to that of the liver lipids, with changes in linoleic acid, eicosatrienoic acid and arachidonic acid appearing at the same times as they occurred in the liver. 6. The results indicated that linoleic acid was preferentially incorporated into the liver phospholipid at the expense of eicosatrienoic acid and oleic acid. The decline in these fatty acids apparently resulted from their competition with linoleic acid for available sites in the phospholipids rather than from any direct replacement by arachidonic acid.